The Influence of Perceived Interactivity and Visual Appeal on Impulse Buying in Beauty Home Services: The Mediating Role of Perceived Enjoyment and A Multi-Group Analysis (MGA) Approach - Shellda Lestari; Antonius Felix (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the relationship between perceived interactivity and visual aesthetics regarding impulse buying, with perceived enjoyment acting as a moderator in the context of beauty home services, and to analyze differences in consumer behavior based on the period of usage (≤ 2 years vs > 2 years). Grounded in the Stimulus-Organism-Response (S-O-R) theory, this explanatory quantitative study employed purposive sampling to collect data from 233 respondents in the Jabodetabek area. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 software. Structural analysis revealed no significant difference in path coefficients between the two groups new users (≤ 2 years) and experienced users (> 2 years). This indicates that, when using the service, both new and long-term users consistently exhibit the same effects, regardless of the duration of their experience.